HBR guide to your professional growth (Boston, Massachusetts : Harvard Business Review Press, 2019)
No one will pay as close attention to your personal growth and development as you will. Whether you're lucky enough to work for an organization that encourages a learning mindset for everyone or whether you're in a place where only a handful of stars get all the heat and light when it comes to professional development, you are the best person to create and monitor your own curriculum. And increasingly in today's workplaces, you are responsible. Without an HR specialist or a personal coach to guide you, how can you assess your own strengths and weaknesses, gather and distill meaningful feedback, set goals for yourself beyond your job duties, gain the new skills you need to stay relevant and excel, nurture your curiosity, and continue to learn, grow, and evolve into your best self at work? Whether your development plan is vague or clear, you can establish a course to acquire and maintain the skills you'll need to be successful and close the gap between where you are now and where you'd like to be.--
Keywords: Career development; Self-culture.